A method for preparing a low thermal expansion coefficient polyimide film for copper clad laminate

The polyimide film prepared by the two-step method solves the problem of high thermal expansion coefficient of the polyimide film, reduces the thermal expansion coefficient, improves the use temperature and mechanical properties, and is suitable for the field of flexible electronics.

CN116874839BActive Publication Date: 2025-04-18HUANGSHAN JINSHIMU PLASTIC TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310703939.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2025-04-18
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The thermal expansion coefficient of polyimide films is high, which leads to mismatch of thermal expansion of materials such as copper and silicon wafers in the field of flexible electronics, which may lead to warping or cracking.

Method used

Polyimide film was prepared by a two-step method. First, the aromatic diamine and dianhydride were polymerized under a nitrogen atmosphere to obtain a polyamic acid solution, and then cast into a film on the surface of the pretreated copper foil, and then dried and heat imidized to obtain a polyimide film with a low thermal expansion coefficient for copper clad plate.

Benefits of technology

It reduces the thermal expansion coefficient of the polyimide film, increases the use temperature of the film, and improves its mechanical properties, and is suitable for insulating, flexible electronics and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004285099990000023
    Figure BDA0004285099990000023
  • Figure BDA0004285099990000081
    Figure BDA0004285099990000081
  • Figure JEAVPV7HBUIRVVEEIBAFXLOWKI7XTIRCQNUND04H
    Figure JEAVPV7HBUIRVVEEIBAFXLOWKI7XTIRCQNUND04H
Patent Text Reader

Abstract

The invention discloses a method for preparing a polyimide film with low thermal expansion coefficient for copper clad laminates, belonging to the technical field of polyimide films, and comprising the following steps: (1) dissolving aromatic dianhydride and aromatic diamine in an organic solvent under a nitrogen atmosphere, wherein the amount ratio of the aromatic dianhydride, the aromatic diamine and the organic solvent is 1 mol:1 mol:3.5 kg, and performing a polymerization reaction at a temperature of 2-8°C for 24-36 hours to obtain a polyamic acid solution; (2) casting the polyamic acid solution on a pretreated copper foil surface to form a film, and sequentially drying and thermal imidizing under nitrogen protection to obtain the polyimide film with low thermal expansion coefficient for copper clad laminates; the invention introduces a rigid naphthalene ring structure and an amide group containing a hydrogen bond into a molecular chain of polyimide, thereby reducing the thermal expansion coefficient of the polyimide film, increasing the use temperature of the film, and the film has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyimide films, and in particular relates to a method for preparing a polyimide film with a low thermal expansion coefficient for a copper-clad laminate. Background Art

[0002] Polyimide is a type of high-performance polymer containing repeating units of aromatic rings and imide rings. It is one of the organic polymers with the best comprehensive performance. Its long-term operating temperature is -200-300°C, and its short-term high temperature resistance can reach above 500°C. It is usually synthesized by polycondensation of precursor compounds containing aromatic diamines and aromatic dianhydrides. The molecular chain of polyimide contains a large number of rigid and random aromatic heterocycles, which give polyimide excellent mechanical properties and thermal stability. It is widely used in aerospace, electronics, medical, energy and other fields.

[0003] In the field of electronics, polyimide is prepared into thin films for the manufacture of thin-film circuit boards, semiconductor packaging materials, and optoelectronic devices. The main products include DuPont's Kapton, Ube Industries' Upilex, and Zhongyuan's Apical. With the continuous advancement of science and technology, electronic products are becoming smaller, lighter, and foldable, which puts higher requirements on the heat resistance, dimensional stability, and flexibility of flexible substrate materials. Due to its excellent comprehensive performance, polyimide has become one of the most promising application materials in the field of flexible substrates. In flexible devices, polyimide must be used in combination with materials such as copper and silicon wafers. If the thermal expansion coefficients of the two materials are different, warping or cracking will occur after the effects of cold and heat. Specifically, the thermal expansion coefficient of copper is 18ppm / ℃, while that of silicon wafers is below 10ppm / ℃. However, the thermal expansion coefficient of ordinary polyimide films is 40-60ppm / ℃, so reducing the thermal expansion coefficient of polyimide films has become one of the research hotspots.

[0004] There are several methods that can be used to reduce the thermal expansion coefficient of polyimide film. The first method is to prepare polyimide film by drawing process, so that the molecular chain is oriented along the drawing direction, thereby reducing the thermal expansion coefficient of the film. The second method is to introduce rigid rod-like structure, hydrogen bond structure and cross-linking structure into polyimide molecules through molecular structure design, which can reduce molecular space hindrance, make the molecular chain stack more tightly and have smaller free volume. However, these methods also have disadvantages. For example, the process of preparing polyimide film by drawing process is relatively complicated, the equipment requirements are also very high, and the produced film has strong anisotropy. Filler modification has disadvantages such as uneven mixing and strict filler size requirements. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a polyimide film with a low thermal expansion coefficient for a copper clad laminate. The polyimide film is prepared by a two-step method and has the characteristics of simple synthesis of diamine monomers, low thermal expansion coefficient of the polyimide film, high operating temperature, excellent mechanical properties, etc., thereby solving the problems in the background technology.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a low thermal expansion coefficient polyimide film for a copper clad laminate comprises the following steps:

[0008] (1) Under a nitrogen atmosphere, an aromatic diamine is dissolved in an organic solvent, and then an aromatic dianhydride is added in multiple portions, wherein the ratio of the aromatic dianhydride, the aromatic diamine and the organic solvent is 1 mol:1 mol:3.5 kg, and a polymerization reaction is carried out at a temperature of 2-8° C. for 24-36 hours to obtain a polyamic acid solution;

[0009] (2) casting the polyamic acid solution on the surface of the pretreated copper foil to form a film, and drying and thermal imidization are performed in sequence under nitrogen protection to obtain a low thermal expansion coefficient polyimide film for copper clad laminates;

[0010] The molecular structure of the aromatic diamine is One of them.

[0011] Furthermore, the aromatic dianhydride is one of pyromellitic dianhydride, biphenyltetracarboxylic dianhydride, hexafluoro dianhydride or diphenyl ether dianhydride.

[0012] Furthermore, the aromatic diamine is prepared by the following steps:

[0013] Step S1, adding diaminonaphthalene, nitrobenzoyl chloride and an organic base into an organic solvent, stirring and reacting at 20-40° C. for 12-24 hours, filtering and drying to obtain an intermediate 1;

[0014] Step S2, the intermediate 1 and stannous chloride are mixed uniformly in a reaction solvent, and then stirred in an oil bath at a temperature of 80-100° C. for reduction reaction for 12-24 hours, and filtered after cooling to room temperature to obtain an aromatic diamine.

[0015] Furthermore, the usage ratio of the diaminonaphthalene, nitrobenzoyl chloride, organic base and organic solvent is 1 mol:2.2-3 mol:2.5-4 mol:5 kg.

[0016] Furthermore, the diaminonaphthalene is one of 1,5-diaminonaphthalene and 2,7-diaminonaphthalene; the nitrobenzoyl chloride is one of p-nitrobenzoyl chloride and m-nitrobenzoyl chloride; and the organic base is one or more of triethylamine, pyridine, and diisopropylethylamine.

[0017] Furthermore, the usage ratio of the intermediate 1, stannous chloride and the reaction solvent is 1 mol:10-20 mol:4.6-9.2 kg; and the reaction solvent is one or more of tetrahydrofuran, ethylene glycol monomethyl ether and ethylene glycol dimethyl ether.

[0018] Furthermore, the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.

[0019] Furthermore, the drying and thermal imidization adopt programmed temperature rise; the drying program is 100℃ / 2h, 120℃ / 2h, 150℃ / 2h, 180℃ / 2h, the imidization program is 200℃ / 0.5h, 250℃ / 0.5h, 300℃ / 0.5h, 400℃ / 0.5h, and the heating rate is 5-10℃ / min.

[0020] Furthermore, the pretreatment method of the copper foil is: first, soak the cleaned and degreased copper foil in a 1 mol / L nitric acid solution for 5 minutes, then transfer to an aromatic diamine solution and soak for 5 minutes, and finally vacuum dry at 60°C and -0.09 to -0.08 MPa for 1 hour. After the copper foil is soaked in the nitric acid solution, an oxide film can be formed on the surface of the copper foil and the roughness can be increased. After soaking in the aromatic diamine solution, the coated polyamic acid can be partially bonded with it, thereby improving the adhesion between the film and the substrate.

[0021] Furthermore, the aromatic diamine solution is an aromatic diamine / N,N-dimethylacetamide solution with a solid content of 30 wt%.

[0022] Beneficial effects of the present invention:

[0023] The invention allows diaminonaphthalene to react with nitrobenzoyl chloride under organic base conditions to obtain an intermediate 1 containing a naphthalene ring and an amide group symmetrically arranged around the naphthalene ring, and then reduces the nitro groups at both ends of the intermediate 1 in the presence of stannous chloride as a reducing agent to obtain an aromatic diamine containing both the naphthalene ring and the amide group; the aromatic diamine is used as a raw material to prepare a low thermal expansion coefficient polyimide film for a copper clad laminate through a two-step method, thereby introducing a rigid naphthalene ring structure and an amide group containing a hydrogen bond into a molecular chain of the polyimide, reducing the thermal expansion coefficient of the polyimide film, increasing the use temperature of the film, and having excellent mechanical properties, the film can be applied to insulation, flexible electronics and other fields;

[0024] The present invention performs surface pretreatment on the copper foil, firstly soaks it in a nitric acid solution to increase the surface roughness of the copper foil, and then soaks it in an N,N-dimethylacetamide solution of an aromatic diamine to provide more chemical sites for subsequent coating of a polyamic acid solution, thereby improving the adhesion between the copper foil and the polyimide film. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] Aromatic diamines are prepared by the following steps:

[0028] Step S1, adding 15.8 g (0.1 mol) of 1,5-diaminonaphthalene, 27.2 g (0.22 mol) of p-nitrobenzoyl chloride and 25.3 g (0.25 mol) of triethylamine to 500 g of N,N-dimethylacetamide, stirring and reacting at 20° C. for 24 h, filtering and drying to obtain 39.4 g of intermediate 1, with a yield of 86.4%;

[0029] Step S2, 22.8 g (0.05 mol) of intermediate 1 and 112.8 g (0.5 mol) of stannous chloride were mixed evenly in 230 g of tetrahydrofuran, and then stirred in an oil bath at 80° C. for reduction reaction for 24 h. After cooling to room temperature, filtration was performed to obtain 15.8 g of aromatic diamine with a yield of 79.5%.

[0030] Example 2

[0031] Aromatic diamines are prepared by the following steps:

[0032] Step S1, adding 15.8 g (0.1 mol) of 1,5-diaminonaphthalene, 30.9 g (0.25 mol) of m-nitrobenzoyl chloride and 23.7 g (0.3 mol) of pyridine to 500 g of N,N-dimethylformamide, stirring and reacting at 25° C. for 16 h, filtering and drying to obtain 37.3 g of intermediate 1, with a yield of 81.7%;

[0033] Step S2, 22.8 g (0.05 mol) of intermediate 1 and 169.2 g (0.75 mol) of stannous chloride were mixed evenly in 300 g of ethylene glycol monomethyl ether, and then stirred in an oil bath at 90° C. for reduction reaction for 18 h. After cooling to room temperature, filtration was performed to obtain 14.3 g of aromatic diamine with a yield of 72.1%.

[0034] Example 3

[0035] Aromatic diamines are prepared by the following steps:

[0036] Step S1, adding 15.8 g (0.1 mol) of 2,7-diaminonaphthalene, 30.9 g (0.25 mol) of p-nitrobenzoyl chloride and 40.4 g (0.4 mol) of triethylamine to 500 g of dimethyl sulfoxide, stirring and reacting at 25° C. for 16 h, filtering and drying to obtain 41.9 g of intermediate 1, with a yield of 91.9%;

[0037] Step S2, 22.8 g (0.05 mol) of intermediate 1 and 180.5 g (0.8 mol) of stannous chloride were mixed evenly in 400 g of ethylene glycol monomethyl ether, and then stirred in an oil bath at 95° C. for reduction reaction for 15 h. After cooling to room temperature, filtration was performed to obtain 17.0 g of aromatic diamine with a yield of 85.6%.

[0038] Example 4

[0039] Aromatic diamines are prepared by the following steps:

[0040] Step S1, adding 15.8 g (0.1 mol) of 2,7-diaminonaphthalene, 30.9 g (0.25 mol) of m-nitrobenzoyl chloride and 40.4 g (0.4 mol) of triethylamine to 500 g of N-methylpyrrolidone, stirring and reacting at 25° C. for 16 h, filtering and drying to obtain 34.0 g of intermediate 1, with a yield of 74.6%;

[0041] Step S2, 22.8 g (0.05 mol) of intermediate 1 and 225.6 g (1 mol) of stannous chloride were mixed evenly in 460 g of ethylene glycol dimethyl ether, and then stirred in an oil bath at a temperature of 100° C. for reduction reaction for 12 h. After cooling to room temperature, the mixture was filtered to obtain 16.0 g of aromatic diamine with a yield of 80.5%.

[0042] Example 5

[0043] A method for preparing a low thermal expansion coefficient polyimide film for a copper clad laminate comprises the following steps:

[0044] (1) Under a nitrogen atmosphere, 3.96 g (0.01 mol) of the aromatic diamine prepared in Example 1 was dissolved in 35 g of N,N-dimethylformamide, and then 2.94 g (0.01 mol) of biphenyltetracarboxylic dianhydride was added in six portions, and the polymerization reaction was carried out at a temperature of 2° C. for 24 h to obtain a light yellow polyamic acid solution;

[0045] (2) The cleaned and degreased copper foil was immersed in a 1 mol / L nitric acid solution for 5 min, then transferred to an aromatic diamine / N,N-dimethylacetamide solution with a solid content of 30 wt% obtained in Example 1 and immersed for 5 min, and finally dried in vacuum at 60° C. and −0.08 MPa for 1 h to obtain a pretreated copper foil, and the polyamic acid solution was cast on the surface of the pretreated copper foil to form a film, and under nitrogen protection, the drying procedure was 100° C. / 2 h, 120° C. / 2 h, 150° C. / 2 h, and 180° C. / 2 h; the imidization procedure was 200° C. / 0.5 h, 250° C. / 0.5 h, 300° C. / 0.5 h, and 400° C. / 0.5 h, and the heating rate was 5° C. / min, and the copper foil was dried and thermally imidized in sequence to obtain a low thermal expansion coefficient polyimide film for copper clad laminates.

[0046] Example 6

[0047] A method for preparing a low thermal expansion coefficient polyimide film for a copper clad laminate comprises the following steps:

[0048] (1) Under a nitrogen atmosphere, 3.96 g (0.01 mol) of the aromatic diamine prepared in Example 2 was dissolved in 35 g of N,N-dimethylacetamide, and then 4.44 g (0.01 mol) of hexafluorodianhydride was added in four portions, and the polymerization reaction was carried out at a temperature of 4° C. for 30 h to obtain a light yellow polyamic acid solution;

[0049] (2) The cleaned and degreased copper foil was immersed in a 1 mol / L nitric acid solution for 5 min, then transferred to an aromatic diamine / N,N-dimethylacetamide solution with a solid content of 30 wt% obtained in Example 1 and immersed for 5 min, and finally dried in vacuum at 60° C. and −0.08 MPa for 1 h to obtain a pretreated copper foil, and the polyamic acid solution was cast on the surface of the pretreated copper foil to form a film, and under nitrogen protection, the drying procedure was 100° C. / 2 h, 120° C. / 2 h, 150° C. / 2 h, and 180° C. / 2 h; the imidization procedure was 200° C. / 0.5 h, 250° C. / 0.5 h, 300° C. / 0.5 h, and 400° C. / 0.5 h, and the heating rate was 8° C. / min, and the copper foil was dried and thermally imidized in sequence to obtain a low thermal expansion coefficient polyimide film for copper clad laminates.

[0050] Example 7

[0051] A method for preparing a low thermal expansion coefficient polyimide film for a copper clad laminate comprises the following steps:

[0052] (1) Under a nitrogen atmosphere, 3.96 g (0.01 mol) of the aromatic diamine prepared in Example 3 was dissolved in 35 g of dimethyl sulfoxide, and then 2.18 g (0.01 mol) of pyromellitic dianhydride was added in five portions, and a polymerization reaction was carried out at a temperature of 6° C. for 32 h to obtain a light yellow polyamic acid solution;

[0053] (2) The cleaned and degreased copper foil was immersed in a 1 mol / L nitric acid solution for 5 min, then transferred to an aromatic diamine / N,N-dimethylacetamide solution with a solid content of 30 wt% obtained in Example 1 and immersed for 5 min, and finally dried in vacuum at 60° C. and −0.09 MPa for 1 h to obtain a pretreated copper foil, and the polyamic acid solution was cast on the surface of the pretreated copper foil to form a film, and under nitrogen protection, the drying procedure was 100° C. / 2 h, 120° C. / 2 h, 150° C. / 2 h, and 180° C. / 2 h; the imidization procedure was 200° C. / 0.5 h, 250° C. / 0.5 h, 300° C. / 0.5 h, and 400° C. / 0.5 h, and the heating rate was 8° C. / min, and the copper foil was dried and thermally imidized in sequence to obtain a low thermal expansion coefficient polyimide film for copper clad laminates.

[0054] Example 8

[0055] A method for preparing a low thermal expansion coefficient polyimide film for a copper clad laminate comprises the following steps:

[0056] (1) Under a nitrogen atmosphere, 3.96 g (0.01 mol) of the aromatic diamine prepared in Example 4 was dissolved in 35 g of N-methylpyrrolidone, and then 3.10 g (0.01 mol) of diphenyl ether dianhydride was added in five portions, and the polymerization reaction was carried out at a temperature of 8° C. for 36 hours to obtain a light yellow polyamic acid solution;

[0057] (2) The cleaned and degreased copper foil was immersed in a 1 mol / L nitric acid solution for 5 min, then transferred to an aromatic diamine / N,N-dimethylacetamide solution with a solid content of 30 wt% obtained in Example 1 and immersed for 5 min, and finally dried in vacuum at 60° C. and −0.09 MPa for 1 h to obtain a pretreated copper foil, and the polyamic acid solution was cast on the surface of the pretreated copper foil to form a film, and under nitrogen protection, the drying procedure was 100° C. / 2 h, 120° C. / 2 h, 150° C. / 2 h, and 180° C. / 2 h; the imidization procedure was 200° C. / 0.5 h, 250° C. / 0.5 h, 300° C. / 0.5 h, and 400° C. / 0.5 h, and the heating rate was 10° C. / min, and the copper foil was dried and thermally imidized in sequence to obtain a low thermal expansion coefficient polyimide film for copper clad laminates.

[0058] Comparative Example 1

[0059] Compared with Example 7, this comparative example uses an equal molar amount of 2,7-diaminonaphthalene to replace the aromatic diamine prepared in Example 3, and the remaining raw material amounts, preparation steps and parameters are the same.

[0060] Comparative Example 2

[0061] Compared with Example 7, the copper foil in this comparative example is not pretreated, and the remaining preparation steps and parameters are the same.

[0062] Performance tests were performed on Examples 5 to 8 and Comparative Examples 1 to 2. The glass transition temperature of the film was measured using a dynamic thermomechanical analyzer, the thermal expansion coefficient of the film at 50-300°C was measured using a static mechanical analyzer, and the tensile strength of the film was measured using a universal testing machine in accordance with GB / T1040.3-2006 standard; the 5% thermal decomposition temperature of the film was measured using a thermogravimetric analyzer at a heating rate of 10°C / min in a nitrogen atmosphere, and the peel strength of the film was tested by peeling the film at 180° from the starting opening of the film sample using a tensile tester. The results are shown in Table 1:

[0063] Table 1

[0064]

[0065] It can be seen from the data in Table 1 that the polyimide films prepared in Examples 5 to 8 of the present invention have a glass transition temperature greater than 329°C, a thermal expansion coefficient at 50-300°C less than 30ppm / °C, a tensile strength greater than 122MPa, a 5wt% thermal decomposition temperature greater than 599°C, and an overall peel strength greater than 0.88kgf / cm; among them, the polyimide film prepared in Example 6 has a glass transition temperature of 387°C, a tensile strength of 151MPa, a thermal expansion coefficient at 50-300°C of 18ppm / °C, which is very close to the thermal expansion coefficient of copper foil of 18ppm / °C, and a peel strength of 0.95kgf / cm, which has very excellent comprehensive performance and is suitable for the application of double-layer flexible copper clad laminates.

[0066] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a low thermal expansion coefficient polyimide film for a copper clad laminate, characterized in that: The following steps are involved: (1) Under a nitrogen atmosphere, an aromatic diamine is dissolved in an organic solvent, and then an aromatic dianhydride is added in multiple portions, wherein the ratio of the aromatic dianhydride, the aromatic diamine and the organic solvent is 1 mol:1 mol:3.5 kg, and a polymerization reaction is carried out at 2-8° C. for 24-36 hours to obtain a polyamic acid solution; (2) first immersing the cleaned and degreased copper foil in a 1 mol / L nitric acid solution for 5 min, then transferring it to an aromatic diamine solution and immersing it for 5 min, and finally vacuum drying it at 60°C for 1 h to obtain a pretreated copper foil; casting a polyamic acid solution on the surface of the pretreated copper foil to form a film, and then drying and thermal imidizing it in sequence under nitrogen protection to obtain a low thermal expansion coefficient polyimide film for copper clad laminates; The molecular structure of the aromatic diamine is , , , One of; The aromatic diamine is prepared by the following steps: Step S1, adding diaminonaphthalene, nitrobenzoyl chloride and an organic base into an organic solvent, stirring and reacting at 20-40° C. for 12-24 hours, filtering and drying to obtain an intermediate 1; Step S2, the intermediate 1 and stannous chloride are mixed uniformly in a reaction solvent, and then stirred in an oil bath at a temperature of 80-100° C. for reduction reaction for 12-24 hours, and filtered after cooling to room temperature to obtain an aromatic diamine.

2. The method for preparing a low thermal expansion coefficient polyimide film for copper clad laminate according to claim 1, characterized in that: The aromatic dianhydride is one of pyromellitic dianhydride, biphenyltetracarboxylic dianhydride, hexafluoro dianhydride or diphenyl ether dianhydride.

3. The method for preparing a low thermal expansion coefficient polyimide film for copper clad laminate according to claim 1, characterized in that: The usage ratio of the diaminonaphthalene, nitrobenzoyl chloride, organic base and organic solvent is 1 mol: 2.2-3 mol: 2.5-4 mol: 5 kg.

4. The method for preparing a low thermal expansion coefficient polyimide film for copper clad laminate according to claim 1, characterized in that: The diaminonaphthalene is one of 1,5-diaminonaphthalene and 2,7-diaminonaphthalene; the nitrobenzoyl chloride is one of p-nitrobenzoyl chloride and m-nitrobenzoyl chloride; and the organic base is one or more of triethylamine, pyridine and diisopropylethylamine.

5. The method for preparing a low thermal expansion coefficient polyimide film for copper clad laminate according to claim 1, characterized in that: The usage ratio of the intermediate 1, stannous chloride and the reaction solvent is 1 mol:10-20 mol:4.6-9.2 kg; the reaction solvent is one or more of tetrahydrofuran, ethylene glycol monomethyl ether and ethylene glycol dimethyl ether.

6. The method for preparing a low thermal expansion coefficient polyimide film for copper clad laminate according to claim 1, characterized in that: The organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.

7. The method for preparing a low thermal expansion coefficient polyimide film for copper clad laminate according to claim 1, characterized in that: The drying and thermal imidization adopt programmed temperature rise; the drying program is 100℃ / 2h, 120℃ / 2h, 150℃ / 2h, 180℃ / 2h, the imidization program is 200℃ / 0.5h, 250℃ / 0.5h, 300℃ / 0.5h, 400℃ / 0.5h, and the heating rate is 5-10℃ / min.

8. The method for preparing a low thermal expansion coefficient polyimide film for copper clad laminate according to claim 1, characterized in that: The aromatic diamine solution is an aromatic diamine / N,N-dimethylacetamide solution with a solid content of 30 wt%.

Citation Information

Patent Citations

  • Polyimide resin containing cyano groups, and applications thereof in preparing copper-clad laminates

    CN105399950A

  • Modified polyamide acid resin slurry and preparation method thereof, and adhesive-free copper-clad plate

    CN111961202A

  • Polyimide film with low thermal expansion coefficient and preparation method thereof

    CN114015091A

  • new aromatic diamines usable for the preparation of polyamides

    FR1368619A